Antibacterial, Antioxidant activity and Phytochemical studies of Crossandra infundibuliformis leaf extracts - N. Sharmila; N. Gomathi (International Journal of Phytomedicine, 2011)
The aim of the present study was to evaluate Crossandra infundibuliformis (Acanthaceae family) for its antibacterial, antioxidant activity and phytochemical constituents. The leaves of C. infundibuliformis were screened for antibacterial activity against six pathogenic bacteria isolated from clinical samples such as Shigella dysenteria, Pseudomonas aeruginosa, Serratia marcescens, Salmonella typhimurium, Proteus mirabilis & Staphylococcus aureus by extracting them in ethanol, petroleum ether and water. Ethanol extract exhibited inhibition zone against all the pathogens comparable to the standard (Amikacin), whereas no zone of inhibition was observed in petroleum ether and water extracts. Phytochemical analysis showed the presence of flavonoids, saponins, terpenoids, cardiac glycoside, reducing sugars and tannins. The ethanol extract of C. infundibuliformis leaves appeared to be good antioxidant agent with maximum inhibition percentage of 89.27 ±0.284 % at 16µg/ml whereas standard Quercetin showed maximum inhibition percentage of 94.30 ±0.272 % at 22µg/ml.